Ceo2 carrier loaded lacoo3 metal oxide catalyst, and preparation method and application thereof

CN122999210APending Publication Date: 2026-10-30NINGXIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611379588.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]针对现有技术中液相沉淀法和浸渍法制备LaCoO3/CeO2复合金属氧化物催化剂时,容易出现LaCoO3钙钛矿相难以稳定形成、Co3O4等杂相生成、活性组分分散不均等问题本发明的目的是提供一种CeO2载体负载LaCoO3金属氧化物催化剂及其制备方法和应用,该方法基于固相球磨-煅烧与液相超声复合相结合的路线,合成LaCoO3/CeO2,获得兼具高活性与高抗烧结性能的CO氧化材料

Benefits of technology

本发明给出的制备方法是将镧盐和钴盐经球磨得到的金属盐混合物,通过模板剂的分散隔离作用和碱性沉淀剂的沉淀作用,使镧源和钴源充分混合并形成La-Co前驱体,再置于500℃~700℃的温度下煅烧1h~3h,使La-Co前驱体发生固相反应并转化为LaCoO3钙钛矿,该LaCoO3颗粒在制备过程中过度长大、团聚或严重烧结的可能性,并有利于其后续与CeO2纳米颗粒复合形成较好的界面接触,然后将该LaCoO3钙钛矿与CeO2纳米颗粒进行液相超声复合,限制将LaCoO3钙钛矿与CeO2纳米颗粒的质量比,使LaCoO3钙钛矿相中的活性组分与CeO2载体形成有效接触,调节LaCoO3活性组分在CeO2载体表面的负载量和分散状态,从而改善活性组分的分散状态和界面稳定性。减少液相沉淀法或浸渍法中由于不同金属组分水解、沉淀、迁移及煅烧转化行为不同而导致的组成偏析、杂相生成和活性组分分散不均等问题,有利于稳定获得LaCoO3/CeO2复合金属氧化物催化剂,从而有利于提高催化剂在CO氧化反应中的结构稳定性和抗烧结能力。此外,CeO2具有Ce4+和Ce3+氧化还原对和良好的储放氧能力,其表面的缺陷位点及氧空位能够与LaCoO3钙钛矿的活性组分产生界面相互作用。XANES/EXAFS、EELS和XPS结果表明,LaCoO3/CeO2复合后Co的价态及局部配位环境发生变化,以及Ce3+相关物种增加。上述结构特征有利于促进活性氧迁移,提高CO低温氧化反应性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999210A_ABST
    Figure CN122999210A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of heterogeneous catalysts, and particularly relates to a CeO2 carrier loaded LaCoO3 metal oxide catalyst, a preparation method and application thereof. The method comprises the following steps: ball milling lanthanum salt and cobalt salt to obtain a metal salt mixture; adding a template agent to the metal salt mixture, continuing ball milling, adding a precipitator, continuing grinding, and then calcining the ground powder under normal pressure to obtain LaCoO3 perovskite; mixing the LaCoO3 perovskite and CeO2 carrier nanoparticles, ultrasonic dispersing in water to obtain a dispersion liquid, and then centrifuging, washing and drying the dispersion liquid to obtain the CeO2 carrier loaded LaCoO3 catalyst. The present application disperses the metal precursor salt by ball milling under the action of solid-phase ball milling with sodium chloride to obtain perovskite with uniform particles, and then loads the perovskite on the oxide carrier under the action of solid-liquid-solid phase transfer, thereby solving the problems of uneven size, low dispersity and phase separation of the catalyst prepared by the existing preparation method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of heterogeneous catalyst technology, specifically relating to a CeO2-supported LaCoO3 metal oxide catalyst, its preparation method, and its application. Background Technology

[0002] With the increasing demand for environmental governance and clean energy utilization, CO complete oxidation combustion catalysts have significant application value in fields such as automobile exhaust purification, industrial exhaust treatment, and indoor air purification. Traditional precious metal-based catalysts (such as Pt, Pd, Rh, etc.) have high activity, but they are expensive and prone to sintering and deactivation at high temperatures.

[0003] In recent years, non-noble metal catalysts, primarily composed of transition metal oxides, have become a research hotspot due to the high cost and susceptibility to sintering and deactivation at high temperatures associated with noble metal-based catalysts. Examples include LaCoO3 / CeO2 metal oxide catalysts. Currently, LaCoO3 / CeO2 metal oxide catalysts are mostly prepared using liquid-phase precipitation and impregnation methods. However, when using liquid-phase precipitation, the hydrolysis, precipitation, and subsequent calcination transformation behaviors of different metal ions such as La, Co, and Ce in solution vary, easily leading to uneven composition of the precipitate precursor, localized phase separation, and uneven dispersion of the active components. Especially when introducing a CeO2 support system, the La-Co-O component struggles to stably form a well-crystallized LaCoO3 perovskite phase during calcination, easily generating a Co3O4 impurity phase. This affects the effective loading of the LaCoO3 active component on the CeO2 support and its interfacial contact with the support, ultimately reducing the catalyst's structural stability (anti-sintering performance) and catalytic performance. The impregnation method typically involves introducing lanthanum and cobalt sources onto the surface of a CeO2 support followed by drying and calcination. During this process, the distribution of the metal salt solution on the support surface, its migration during drying, and the thermal conversion during calcination all affect the final phase structure and the dispersion state of the active components. When the La and Co components fail to reach sufficient contact and undergo a homogeneous solid-phase reaction, impurity phases such as Co3O4 are easily formed, making it difficult to stably obtain the LaCoO3 perovskite phase. These issues weaken the interfacial interaction between LaCoO3 and CeO2, reduce the migration capacity of reactive oxygen species, and consequently affect the low-temperature catalytic activity and structural stability (anti-sintering performance) of the catalyst. Summary of the Invention

[0004] To address the problems encountered in existing technologies for preparing LaCoO3 / CeO2 composite metal oxide catalysts using liquid-phase precipitation and impregnation methods, such as the difficulty in stabilizing the LaCoO3 perovskite phase, the formation of impurity phases like Co3O4, and uneven dispersion of active components, the purpose of this invention is to provide a CeO2-supported LaCoO3 metal oxide catalyst, its preparation method, and its application. This method is based on a route combining solid-phase ball milling-calcination with liquid-phase ultrasonication to synthesize LaCoO3 / CeO2, obtaining a CO oxidation material with both high activity and high anti-sintering properties.

[0005] To address the aforementioned technical problems, this invention provides a method for preparing a CeO2-supported LaCoO3 catalyst, comprising the following steps: Lanthanum salt and cobalt salt were ball-milled to obtain a metal salt mixture, wherein the molar ratio of lanthanum salt to cobalt salt was 0.8~1.2:1.0; The formation of LaCoO3 perovskite requires a close stoichiometric ratio of La and Co. Excessive deviation in the La and Co ratios can lead to incomplete formation of the LaCoO3 perovskite phase and the potential formation of La2O3, Co3O4, or other La-Co-O intermediate phases. Therefore, limiting the molar ratio of La to Co to 0.8–1.2:1 is beneficial for promoting the formation of the LaCoO3 perovskite phase.

[0006] A template agent is added to a metal salt mixture and ball milling continues. After grinding, an alkaline precipitant is added and ball milling continues. The resulting ball-milled powder is calcined at 500℃~700℃ under normal pressure for 1h~3h to obtain LaCoO3 perovskite. The alkaline precipitant provides OH- - The molar ratio of La to Co is 4.4~5.6:0.8~1.2:1; LaCoO3 perovskite and CeO2 nanoparticles were mixed and then added to deionized water for ultrasonic dispersion. The ultrasonic dispersion was centrifuged, washed and dried to obtain a CeO2-supported LaCoO3 catalyst, wherein the mass ratio of LaCoO3 perovskite to CeO2 nanoparticles was 0.01~0.1:1.

[0007] Lanthanum and cobalt salts were used as raw materials for preparing LaCoO3 perovskite. Lanthanum and cobalt sources were thoroughly mixed and formed a La-Co precursor through ball milling assisted by a template agent and an alkaline precipitant. The precursor was then calcined at 500℃~700℃ for 1h~3h to allow a solid-state reaction and transformation into the LaCoO3 perovskite phase. The pre-prepared LaCoO3 perovskite was then ultrasonically composited with CeO2 nanoparticles in the liquid phase to obtain a metal oxide catalyst with effective LaCoO3 and CeO2 composite.

[0008] Template agents are primarily used as solid dispersion media to promote full contact between lanthanum and cobalt sources during ball milling and improve the dispersion state of the La-Co precursor. Alkaline precipitants can provide OH- - This process allows the lanthanum and cobalt sources to form La-containing hydroxide or hydroxylated precursors and Co-containing hydroxide or hydroxylated precursors, which is beneficial for the formation of the LaCoO3 perovskite phase during subsequent calcination. Calcination temperature and time also influence the formation of the LaCoO3 perovskite phase. If the calcination temperature is too low or the calcination time is too short, the LaCoO3 perovskite phase may not form sufficiently, easily leaving behind cobalt oxides, lanthanum oxides, or La-Co-O intermediate phases. If the calcination temperature is too high or the calcination time is too long, the LaCoO3 grains are prone to further growth, agglomeration, or sintering. Therefore, controlling the calcination temperature to 500℃~700℃ and the calcination time to 1h~3h is beneficial for promoting the formation of the LaCoO3 perovskite phase while reducing the possibility of excessive particle growth and severe sintering, and also facilitates better interfacial contact between the LaCoO3 and CeO2 nanoparticles in subsequent compositing.

[0009] Furthermore, this invention mixes pre-prepared LaCoO3 perovskite and CeO2 nanoparticles in a liquid phase and promotes sufficient contact between the two through ultrasonic dispersion. By controlling the mass ratio of LaCoO3 perovskite to CeO2 nanoparticles to 0.01~0.1:1, the loading and dispersion state of the LaCoO3 active component on the CeO2 support surface can be adjusted. If the LaCoO3 content is too low (mass ratio of LaCoO3 perovskite to CeO2 nanoparticles less than 0.01:1), the amount of active component is insufficient, which may lead to limited improvement in catalytic activity; if the LaCoO3 content is too high (mass ratio of LaCoO3 perovskite to CeO2 nanoparticles greater than 0.1:1), the possibility of direct contact and local aggregation between LaCoO3 particles increases, which is not conducive to the dispersion of active component and the stability of interface structure. Therefore, controlling the mass ratio of LaCoO3 to CeO2 nanoparticles within the above range is beneficial to balance the loading of active component, dispersion state, and LaCoO3 / CeO2 heterogeneous interface construction.

[0010] Preferably, the lanthanum salt and the cobalt salt are both nitrates, chlorides, or acetates; more preferably, the lanthanum salt and the cobalt salt are both chlorides.

[0011] Lanthanum and cobalt salts are selected from nitrates, chlorides, or acetates because these metal salts are widely available, easily mixed with the template agent and alkaline precipitant during ball milling, and can be converted into the corresponding La-Co-O precursors during subsequent calcination, thus facilitating the formation of the LaCoO3 perovskite phase. Nitrates typically have good thermal decomposition characteristics, which is beneficial for the subsequent formation of oxide crystal phases; chlorides are inexpensive, readily available, and have good compatibility with the sodium chloride template agent system; acetates are easily decomposed during heat treatment, and their decomposition products are relatively volatile, which helps reduce the impact of some residual impurities. Therefore, all of the above salts can be used as metal sources for preparing LaCoO3 perovskite. More preferably, the lanthanum and cobalt salts are both chlorides. Chlorides and sodium chloride template agents belong to the same anionic system, which can reduce the introduction of additional anions; at the same time, after the addition of the alkaline precipitant, chloride ions can form water-soluble sodium chloride with sodium ions, which is convenient for subsequent washing and removal, thus helping to reduce impurity residues and obtain well-dispersed LaCoO3 perovskite particles.

[0012] Preferably, the molar ratio of the lanthanum salt to the cobalt salt is 1:1.

[0013] The formation of LaCoO3 perovskite requires a close stoichiometric ratio of La and Co. Excessive deviation in the La and Co element ratios can lead to incomplete formation of the LaCoO3 perovskite phase and the easy formation of La2O3, Co3O4, or other La-Co-O intermediate phases. Therefore, limiting the molar ratio of La to Co to 0.8–1.2:1 is beneficial for promoting the formation of the LaCoO3 perovskite phase; a further preferred ratio is 1:1, which better matches the theoretical stoichiometric composition of LaCoO3.

[0014] Preferably, the template agent is one of potassium chloride, sodium bromide, or sodium chloride, and more preferably sodium chloride is used as the template agent. The template agent is mainly used as a solid dispersion medium and a spatial isolator. During ball milling, the template agent promotes full contact between the lanthanum and cobalt sources and improves the dispersion state of the precursor. During subsequent calcination, the template agent can isolate the La-Co precursor particles to a certain extent, reducing the possibility of direct contact, aggregation, and excessive growth between particles, thus facilitating the acquisition of well-dispersed LaCoO3 perovskite particles. Potassium chloride, sodium bromide, and sodium chloride, among other template agents, can act as physical isolators, reducing direct contact between La-Co precursor particles. These template agents also exhibit good removability, easily removing them from the system after calcination and washing. Sodium chloride is further preferred as a template agent because it is widely available, inexpensive, chemically stable, and has excellent water solubility, allowing it to be removed by washing after the reaction, thereby reducing template agent residue in the final product. The introduction of sodium chloride helps improve the dispersion state of the LaCoO3 precursor, reduces particle agglomeration during calcination, and promotes better interfacial contact between LaCoO3 and CeO2 nanoparticles.

[0015] Preferably, the mass ratio of LaCoO3 perovskite to CeO2 nanoparticles is 0.01 to 0.1:1, and more preferably 0.05:1.

[0016] The mass ratio of LaCoO3 perovskite to CeO2 nanoparticles is controlled at 0.01~0.1:1, with a preferred ratio of 0.05:1. This is because at this ratio, the LaCoO3 active component can be well loaded onto the CeO2 support surface and form an effective interfacial contact with CeO2. If the LaCoO3 content is too low, the amount of active component will be insufficient, which may lead to limited improvement in catalytic activity; if the LaCoO3 content is too high, the possibility of direct contact and local aggregation between LaCoO3 particles increases, which is not conducive to the dispersion of active component and the stability of the interfacial structure. Therefore, controlling the mass ratio of LaCoO3 perovskite to CeO2 nanoparticles at 0.01~0.1:1, and more preferably 0.05:1, is beneficial to balance the loading of active component, dispersion state, and the construction of LaCoO3 / CeO2 heterogeneous interface.

[0017] Preferably, the calcination temperature for preparing LaCoO3 perovskite is 500℃~700℃, and the calcination time is 1h~3h. More preferably, the calcination temperature for LaCoO3 perovskite is 600℃, and the calcination time is 2h.

[0018] In this embodiment, a calcination temperature of 600°C and a calcination time of 2 hours for LaCoO3 perovskite are used to obtain the LaCoO3 perovskite crystalline phase. These calcination conditions provide appropriate thermal energy for the solid-state reaction between the lanthanum and cobalt sources, which is beneficial for the formation and crystallization of the LaCoO3 perovskite phase. Compared to excessively low temperatures or short times, a calcination temperature of 600°C and a calcination time of 2 hours for LaCoO3 perovskite are more conducive to the complete transformation of the precursor. Simultaneously, compared to excessively high temperatures or long times, these conditions reduce the possibility of excessive growth, agglomeration, or sintering of LaCoO3 particles, thereby facilitating the subsequent composite formation of LaCoO3 and CeO2 nanoparticles and the formation of a better interfacial contact.

[0019] This invention provides a method for preparing a CeO2-supported LaCoO3 catalyst.

[0020] This invention also provides the application of a CeO2-supported LaCoO3 catalyst in the CO oxidation reaction.

[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: The preparation method provided in this invention involves ball milling a mixture of lanthanum and cobalt salts to obtain a metal salt mixture. Through the dispersion and isolation effect of a template agent and the precipitation effect of an alkaline precipitant, the lanthanum and cobalt sources are fully mixed to form a La-Co precursor. This precursor is then calcined at 500℃~700℃ for 1h~3h to allow a solid-phase reaction, transforming the La-Co precursor into LaCoO3 perovskite. This process minimizes the possibility of excessive growth, agglomeration, or severe sintering of the LaCoO3 particles, and facilitates better interfacial contact between the LaCoO3 perovskite and CeO2 nanoparticles. The LaCoO3 perovskite is then combined with CeO2 nanoparticles via liquid-phase ultrasonication. This limits the mass ratio of LaCoO3 perovskite to CeO2 nanoparticles, ensuring effective contact between the active components in the LaCoO3 perovskite phase and the CeO2 support. This regulates the loading and dispersion state of the LaCoO3 active components on the CeO2 support surface, thereby improving the dispersion state and interfacial stability of the active components. Reducing the problems of compositional segregation, impurity phase formation, and uneven dispersion of active components caused by different hydrolysis, precipitation, migration, and calcination transformation behaviors of different metal components in liquid-phase precipitation or impregnation methods is beneficial for the stable acquisition of LaCoO3 / CeO2 composite metal oxide catalysts, thereby improving the structural stability and anti-sintering ability of the catalyst in the CO oxidation reaction. Furthermore, CeO2 possesses Ce... 4+ and Ce 3+LaCoO3 perovskite exhibits excellent redox pairs and a good oxygen storage and release capacity. Its surface defect sites and oxygen vacancies can interact with the active components of the perovskite. XANES / EXAFS, EELS, and XPS results indicate that the valence state and local coordination environment of Co change after the LaCoO3 / CeO2 composite, as well as the CeO2 composition... 3+ The number of related species has increased. The above structural features are conducive to promoting the migration of reactive oxygen species and improving the performance of CO oxidation at low temperatures.

[0022] Therefore, the preparation method provided by this invention can obtain a LaCoO3 / CeO2 supported metal oxide catalyst with effective composite of LaCoO3 and CeO2, good interfacial contact, high dispersion of active components, and good structural stability. This catalyst exhibits good low-temperature catalytic activity and anti-sintering ability in the CO oxidation reaction. The preparation method is simple and has the potential for further scale-up preparation and industrial application. Attached Figure Description

[0023] Figure 1 The images shown are transmission electron microscope (TEM) images and mapping diagrams of the 5%-LaCoO3 / CeO2 catalyst prepared in Example 1 of this invention. In the images, a is a TEM image of the 5%-LaCoO3 / CeO2 catalyst prepared in Example 1, b is a STEM image of the 5%-LaCoO3 / CeO2 catalyst prepared in Example 1, c is a La element mapping diagram, d is a Ce element mapping diagram, e is a Co element mapping diagram, and f is an O element mapping diagram.

[0024] Figure 2 The figures show the catalytic activity data of 5%-LaCoO3 / CeO2, 5%-LaCoO3 / AlO(OH), and 5%-LaCoO3 / SiO2 obtained in Examples 1, 1, and 2 of the present invention, respectively.

[0025] Figure 3 This is a comparative catalytic activity data chart of 5wt.%-LaCoO3 / CeO2, 5wt.%-LaCoO3 / CeO2-1, and 5wt.%-LaCoO3 / CeO2-2 prepared in Examples 1, 2, and 3 of the present invention, respectively.

[0026] Figure 4 The 5wt.%-LaCoO3 / CeO2 and 1wt.%-LaCoO3 / CeO2 prepared in Examples 1, 4 and 5 of this invention, respectively 2, Catalytic activity data for 10wt.%-LaCoO3 / CeO2.

[0027] Figure 5The graph shows the anti-sintering performance data of 5%-LaCoO3 / CeO2 obtained in Example 1 of the present invention.

[0028] Figure 6 The XRD pattern is shown in Example 1 of this invention, representing the synthesis process of 5%-LaCoO3 / CeO2.

[0029] Figure 7 The XRD pattern is shown for the synthesis process of 5%-LaCoO3 / AlO(OH) prepared in Comparative Example 1 of the present invention.

[0030] Figure 8 The XRD pattern is shown for the synthesis process of 5%-LaCoO3 / SiO2 obtained in Comparative Example 2 of the present invention.

[0031] Figure 9 The image shows the XRD pattern of the synthesis process of LaCoO3 perovskite in Example 1 of this invention.

[0032] Figure 10 The XRD pattern is shown in the synthesis process of LaCoO3 / CeO2 prepared without NaCl template as described in Comparative Example 3 of the present invention.

[0033] Figure 11 This is a comparison chart of the activities of the 5% LaCoO3 / CeO2 catalyst prepared without NaCl template in Comparative Example 3 of the present invention and the 5%-LaCoO3 / CeO2 catalyst prepared in Example 1.

[0034] Figure 12 The XRD pattern of the synthesis process of LaCoO3 / CeO2 prepared by impregnation method in Comparative Example 4 of the present invention is shown.

[0035] Figure 13 The XRD pattern is shown in Comparative Example 5 of this invention, which shows the synthesis process of LaCoO3 / CeO2 prepared by precipitation method.

[0036] Figure 14 The synchrotron radiation X-ray absorption spectrum test results of the 5% LaCoO3 / CeO2 catalyst prepared in Example 1 of the present invention are shown in (a) Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum (La K-edge); (b) X-ray absorption near-edge structure (XANES) spectrum (Co K-edge); and (c) Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum.

[0037] Figure 15The results of aberration-corrected scanning transmission electron microscopy and electron energy loss spectroscopy of the 5% LaCoO3 / CeO2 catalyst prepared in Example 1 of the present invention are shown; (a) is a HAADF-STEM image; (b) is an EELS M4 / M5 ratio mapping (CeM4,5 edge).

[0038] Figure 16 The image shows a comparison of Ce 3d XPS between the 5% LaCoO3 / CeO2 catalyst prepared in Example 1 of this invention and pure CeO2. Detailed Implementation

[0039] The specific embodiments of the present invention are described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention. Unless otherwise specified, the experimental methods described in the embodiments of the present invention are conventional methods.

[0040] It should be noted that when numerical ranges are involved in this invention, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in Examples 1 to 7, preferred embodiments are described in this invention to avoid redundancy. However, this invention is not limited to these, but can be implemented in other ways within the scope of the technical solutions defined in the appended claims. All raw materials, reagents, instruments, and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.

[0041] The following detailed description, in conjunction with embodiments of the present invention and accompanying drawings, provides a clear and complete illustration of the technical solutions in these embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0042] Example 1 A method for preparing a CeO2-supported LaCoO3 catalyst includes the following steps: First, add a mixture of 1 mmol lanthanum chloride and 1 mmol cobalt chloride to a 50 mL stainless steel reactor. At the same time, add four large stainless steel balls with a diameter of 20 mm and twelve small stainless steel balls with a diameter of 10 mm. Grind at 300 rpm for 5 min to obtain a metal salt mixture.

[0043] Add sodium chloride as a template to the metal salt mixture and continue grinding for 30 min. Then add 5 mmol of NaOH as a precipitant and continue grinding for 30 min. Calcine the resulting powder at 600 °C under normal pressure for 2 h to obtain LaCoO3 perovskite.

[0044] 50 mg of LaCoO3 perovskite and 1 g of CeO2 were placed in a 100 mL beaker, deionized water was added, and the mixture was ultrasonically dispersed to obtain a dispersion. The dispersion was centrifuged, washed, and dried to obtain a CeO2-supported LaCoO3 catalyst, named 5%-LaCoO3 / CeO2.

[0045] Example 2 A method for preparing a CeO2-supported LaCoO3 catalyst includes the following steps: First, a mixture of 1 mmol lanthanum acetate and 1 mmol cobalt acetate was added to a 50 mL stainless steel reactor. At the same time, four large stainless steel balls with a diameter of 20 mm and twelve small stainless steel balls with a diameter of 10 mm were added. The mixture was ground at 280 rpm for 8 min to obtain a metal salt mixture.

[0046] Add sodium chloride as a template to the obtained metal salt mixture, continue grinding for 30 min, then add 5 mmol of NaOH as a precipitant, and continue grinding for 30 min; calcine the resulting powder at 700℃ under normal pressure for 3 h to obtain LaCoO3 perovskite.

[0047] 50 mg of LaCoO3 perovskite and 1 g of CeO2 were placed in a 100 mL beaker, deionized water was added, and the mixture was ultrasonically dispersed to obtain a dispersion. The dispersion was centrifuged, washed, and dried to obtain a CeO2-supported LaCoO3 catalyst, named 5%-LaCoO3 / CeO2-1.

[0048] Example 3 A method for preparing a CeO2-supported LaCoO3 catalyst includes the following steps: First, add a mixture of 1 mmol lanthanum nitrate and 1 mmol cobalt nitrate to a 50 mL stainless steel reactor. At the same time, add four large stainless steel balls with a diameter of 20 mm and twelve small stainless steel balls with a diameter of 10 mm. Grind at 300 rpm for 5 min to obtain a metal salt mixture.

[0049] Add sodium chloride as a template to the metal salt mixture and continue grinding for 30 min. Then add 5 mmol of NaOH as a precipitant and continue grinding for 30 min. Calcine the resulting powder at 500 °C under normal pressure for 1 h to obtain LaCoO3 perovskite.

[0050] 50 mg of LaCoO3 perovskite and 1 g of CeO2 were placed in a 100 mL beaker, deionized water was added, and the mixture was ultrasonically dispersed to obtain a dispersion. The dispersion was centrifuged, washed, and dried to obtain a CeO2-supported LaCoO3 catalyst, named 5%-LaCoO3 / CeO2-2.

[0051] Example 4 A method for preparing a CeO2-supported LaCoO3 catalyst includes the following steps: First, add a mixture of 1 mmol lanthanum chloride and 1 mmol cobalt chloride to a 50 mL stainless steel reactor. At the same time, add four large stainless steel balls with a diameter of 20 mm and twelve small stainless steel balls with a diameter of 10 mm. Grind at 300 rpm for 5 min to obtain a metal salt mixture.

[0052] Add sodium chloride as a template to the metal salt mixture and continue grinding for 30 min. Then add 5 mmol of NaOH as a precipitant and continue grinding for 30 min. Calcine the resulting powder at 600 °C under normal pressure for 2 h to obtain LaCoO3 perovskite.

[0053] 10 mg of LaCoO3 perovskite and 1 g of CeO2 were placed in a 100 mL beaker, deionized water was added, and the mixture was ultrasonically dispersed to obtain a dispersion. The dispersion was centrifuged, washed, and dried to obtain a CeO2-supported LaCoO3 catalyst, named 1%-LaCoO3 / CeO2.

[0054] Example 5 A method for preparing a CeO2-supported LaCoO3 catalyst includes the following steps: First, add a mixture of 1 mmol lanthanum chloride and 1 mmol cobalt chloride to a 50 mL stainless steel reactor. At the same time, add four large stainless steel balls with a diameter of 20 mm and twelve small stainless steel balls with a diameter of 10 mm. Grind at 300 rpm for 5 min to obtain a metal salt mixture.

[0055] Add sodium chloride as a template to the metal salt mixture and continue grinding for 30 min. Then add 5 mmol of NaOH as a precipitant and continue grinding for 30 min. Calcine the resulting powder at 600 °C under normal pressure for 2 h to obtain LaCoO3 perovskite.

[0056] 100 mg of LaCoO3 perovskite and 1 g of CeO2 were placed in a 100 mL beaker, deionized water was added, and the mixture was ultrasonically dispersed to obtain a dispersion. The dispersion was centrifuged, washed, and dried to obtain a CeO2-supported LaCoO3 catalyst, named 10%-LaCoO3 / CeO2.

[0057] Example 6 A method for preparing a CeO2-supported LaCoO3 catalyst includes the following steps: First, a mixture of 0.8 mmol lanthanum chloride and 1 mmol cobalt chloride was added to a 50 mL stainless steel reactor. At the same time, four large stainless steel balls with a diameter of 20 mm and twelve small stainless steel balls with a diameter of 10 mm were added. The mixture was ground at 300 rpm for 5 min to obtain a metal salt mixture.

[0058] Sodium chloride, a template agent, was added to the obtained metal salt mixture, and grinding was continued for 30 min. Then, 4.4 mmol of NaOH, a precipitant, was added, and grinding was continued for 30 min. The resulting powder was calcined at 600 °C under normal pressure for 2 h to obtain LaCoO3 perovskite.

[0059] 50 mg of LaCoO3 perovskite and 1 g of CeO2 were placed in a 100 mL beaker, deionized water was added, and the mixture was ultrasonically dispersed to obtain a dispersion. The dispersion was centrifuged, washed, and dried to obtain a CeO2-supported LaCoO3 catalyst, named 5%-LaCoO3 / CeO2.

[0060] Example 7 A method for preparing a CeO2-supported LaCoO3 catalyst includes the following steps: First, a mixture of 1.2 mmol lanthanum chloride and 1 mmol cobalt chloride was added to a 50 mL stainless steel reactor. At the same time, four large stainless steel balls with a diameter of 20 mm and twelve small stainless steel balls with a diameter of 10 mm were added. The mixture was ground at 300 rpm for 5 min to obtain a metal salt mixture.

[0061] Add sodium chloride as a template to the metal salt mixture and continue grinding for 30 min. Then add 5.6 mmol of NaOH as a precipitant and continue grinding for 30 min. Calcine the resulting powder at 600 °C under normal pressure for 2 h to obtain LaCoO3 perovskite.

[0062] 50 mg of LaCoO3 perovskite and 1 g of CeO2 were placed in a 100 mL beaker, deionized water was added, and the mixture was ultrasonically dispersed to obtain a dispersion. The dispersion was centrifuged, washed, and dried to obtain a CeO2-supported LaCoO3 catalyst, named 5%-LaCoO3 / CeO2.

[0063] Comparative Example 1 A method for preparing an AlO(OH)-supported perovskite LaCoO3 catalyst includes the following steps: First, add 1 mmol of lanthanum chloride and 1 mmol of cobalt chloride to a 50 mL stainless steel ball mill jar, and add four large stainless steel balls with a diameter of 20 mm and twelve small stainless steel balls with a diameter of 10 mm. Grind at 300 rpm for 5 min to obtain a metal salt mixture. After the initial ball milling, sodium chloride, a template agent, was added, and milling continued for 30 minutes. Then, 5 mmol of NaOH, a precipitant, was added, and milling continued for another 30 minutes. The powder was then calcined at 600°C under normal pressure for 2 hours to obtain perovskite.

[0064] Then, 50 mg of perovskite and 1 g of AlO(OH) were placed in a 100 mL beaker and dispersed in deionized water by ultrasonic treatment. The mixture was then centrifuged, washed, and dried to obtain a sample of AlO(OH)-supported perovskite LaCoO3 catalyst, named 5%-LaCoO3 / AlO(OH).

[0065] Comparative Example 2 A method for preparing a silica-supported perovskite LaCoO3 catalyst includes the following steps: First, add 1 mmol of lanthanum chloride and 1 mmol of cobalt chloride to a 50 mL stainless steel reactor, and simultaneously add four large stainless steel balls with a diameter of 20 mm and twelve small stainless steel balls with a diameter of 10 mm. Grind at 300 rpm for 5 min to obtain a metal salt mixture. After the initial ball milling, sodium chloride, a template agent, was added to the reactor, and milling continued for 30 minutes. Then, 5 mmol of NaOH, a precipitant, was added, and milling continued for 30 minutes. The powder was then calcined at 600°C under normal pressure for 2 hours to obtain perovskite.

[0066] Then, 50 mg of perovskite and 1 g of SiO2 were placed in a 100 mL beaker and dispersed in deionized water by ultrasonic treatment. The mixture was then centrifuged, washed, and dried to obtain a sample of silica-supported perovskite (LaCoO3) catalyst, named 5%-LaCoO3 / SiO2.

[0067] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that no template agent was added.

[0068] A method for preparing a CeO2-supported LaCoO3 catalyst includes the following steps: First, add a mixture of 1 mmol lanthanum chloride and 1 mmol cobalt chloride to a 50 mL stainless steel reactor. At the same time, add four large stainless steel balls with a diameter of 20 mm and twelve small stainless steel balls with a diameter of 10 mm. Grind at 300 rpm for 5 min to obtain a metal salt mixture.

[0069] Add 5 mmol of NaOH precipitant to the obtained metal salt mixture and grind for 30 min; calcine the resulting ground powder at 600℃ under normal pressure for 2 h to obtain LaCoO3 perovskite.

[0070] 50 mg of LaCoO3 perovskite and 1 g of CeO2 were placed in a 100 mL beaker, deionized water was added, and the mixture was ultrasonically dispersed to obtain a dispersion. The dispersion was centrifuged, washed, and dried to obtain a CeO2-supported LaCoO3 catalyst, named 5%-LaCoO3 / CeO2.

[0071] Comparative Example 4 Comparative Example 4 shows LaCoO3 / CeO2 prepared by the impregnation method.

[0072] A method for preparing LaCoO3 / CeO2 by impregnation includes the following steps: Lanthanum nitrate and cobalt nitrate were dissolved in 100 ml of deionized water and stirred until completely dissolved to obtain a lanthanum-cobalt mixed salt solution. CeO2 nanoparticles were added to the above lanthanum-cobalt mixed salt solution and stirred at room temperature for 2 h to allow the lanthanum and cobalt sources to fully impregnate the surface of the CeO2 nanoparticles. The resulting mixture was then heated to dryness at 80 °C and dried further at 80 °C for 12 h to obtain the impregnation precursor. The obtained impregnation precursor was placed in a muffle furnace and calcined at 600 °C under normal pressure for 2 h. After cooling to room temperature, the LaCoO3 / CeO2 catalyst prepared by the impregnation method was obtained, denoted as LaCoO3 / CeO2-IM.

[0073] Comparative Example 5 Comparative Example 5 shows LaCoO3 / CeO2 prepared by precipitation method.

[0074] A method for preparing LaCoO3 / CeO2 by precipitation includes the following steps: Lanthanum nitrate and cobalt nitrate were dissolved in 100 ml of deionized water and stirred until completely dissolved to obtain a lanthanum-cobalt mixed salt solution. CeO2 nanoparticles were added to the above lanthanum-cobalt mixed salt solution and stirred at room temperature for 2 h. Under continuous stirring, NaOH solution was slowly added dropwise to the above mixture to adjust the pH of the system to 10-11, and stirring was continued for aging for 6 h to allow the La and Co components to precipitate on or near the surface of the CeO2 nanoparticles. The obtained precipitate was then separated by centrifugation and washed with deionized water. The obtained solid was dried at 80 °C for 12 h to obtain the precipitation precursor. The obtained precipitation precursor was placed in a muffle furnace and calcined at 600 °C under normal pressure for 2 h. After cooling to room temperature, the LaCoO3 / CeO2 catalyst prepared by precipitation method was obtained, denoted as LaCoO3 / CeO2-CP.

[0075] Experimental Test Figure 1 The images shown are transmission electron microscope (TEM) images and mapping images of 5%-LaCoO3 / CeO2 obtained in Example 1 of this invention. Figure 1 In the image, 'a' is a TEM image of the 5%-LaCoO3 / CeO2 catalyst prepared in Example 1; Figure 1 In this context, 'b' represents the corresponding STEM image. Figure 1 In this context, 'c' represents the La element mapping diagram. Figure 1 In this context, d represents the Ce element mapping diagram; Figure 1 In this context, 'e' represents the mapping diagram of the Co element. Figure 1 In this context, f represents the O-element mapping. (The rest of the text appears to be a fragment and requires further context for accurate translation.) Figure 1 a and Figure 1 As can be seen from b, the obtained catalyst contains square LaCoO3 particles that are in contact with the CeO2 support region. Figure 1 c~ Figure 1 As can be seen from f, La, Co, Ce and O elements are all present in the sample. Among them, La and Co elements have a good spatial correspondence in the corresponding regions of LaCoO3 particles, Ce element is distributed in the support region, and O element is distributed in the entire oxide system. This indicates that the method of the present invention successfully prepared the LaCoO3 / CeO2 composite metal oxide catalyst, and there is good interfacial contact between the LaCoO3 active component and the CeO2 support.

[0076] Figure 2 The catalytic activity spectra of 5%-LaCoO3 / CeO2 (LaCoO3 / CeO2-SLS), 5%-LaCoO3 / AlO(OH) (LaCoO3 / AlO(OH)-SLS), and 5%-LaCoO3 / SiO2 (LaCoO3 / SiO2-SLS) prepared in Example 1, Comparative Example 1, and Comparative Example 2 of the present invention are shown. The LaCoO3 / CeO2-SLS catalyst exhibits excellent low-temperature activity, with its T... 90 The temperature required to achieve 90% CO conversion is approximately 210°C. In comparison, the temperature required for LaCoO3 / SiO2-SLS and LaCoO3 / AlO(OH)-SLS is... 90 These are significantly higher, at approximately 330°C and 340°C respectively. (Through...) Figure 2 It is known that 5%-LaCoO3 / CeO2-SLS has the best performance. The method of the present invention successfully stimulates the synergistic effect between LaCoO3 and CeO2 support, enabling the catalyst to efficiently convert CO at a lower temperature.

[0077] Figure 3This is a comparison of the activity data of 5wt.%-LaCoO3 / CeO2, 5wt.%-LaCoO3 / CeO2-1, and 5wt.%-LaCoO3 / CeO2-2 prepared in Examples 1, 2, and 3 of the present invention, respectively. Figure 3 It can be seen that the 5wt.%LaCoO3 / CeO2-SLS catalyst exhibits excellent CO oxidation performance, with its T 90 The temperature required to achieve 90% CO conversion is approximately 210°C.

[0078] Figure 4 These are the activity comparison data of 5wt.%-LaCoO3 / CeO2, 1wt.%-LaCoO3 / CeO2, and 10wt.%-LaCoO3 / CeO2 obtained in Examples 1, 4, and 5 of this invention, respectively. Figure 4 It can be seen that the 5wt.%LaCoO3 / CeO2-SLS catalyst exhibits excellent CO oxidation performance, with its T 90 The temperature required to achieve 90% CO conversion is approximately 210°C.

[0079] Figure 5 This refers to the anti-sintering activity data of 5%-LaCoO3 / CeO2 obtained in Example 1 of the present invention, obtained through... Figure 5 It can be seen that the 5%-LaCoO3 / CeO2 catalyst prepared in this invention exhibits excellent anti-sintering properties, and its activity even improves after high-temperature treatment at 800℃. However, the activity of pure LaCoO3 decreases significantly after high-temperature sintering, indicating that it does not possess anti-sintering ability.

[0080] Figure 6 This is the XRD pattern of the synthesis process of 5%-LaCoO3 / CeO2 obtained in Example 1 of this invention. Figure 6 The composition of crystal phases in different preparation stages and components was revealed in detail. After washing away sodium chloride, perovskite peaks appeared. LaCoO3 was successfully synthesized and has good crystallinity. This method successfully constructed a composite structure composed of LaCoO3 and CeO2.

[0081] Figure 7 This is the XRD pattern of the synthesis process of 5%-LaCoO3 / AlO(OH) obtained in Comparative Example 1 of the present invention. Figure 7 The composition of crystal phases in different preparation stages and components was revealed in detail. After washing away sodium chloride, perovskite peaks appeared. LaCoO3 was successfully synthesized and has good crystallinity. A composite structure composed of LaCoO3 and AlO(OH) was successfully constructed by SLS (solid-liquid-solid) method.

[0082] Figure 8This is the XRD pattern of the synthesis process of 5%-LaCoO3 / SiO2 obtained in Comparative Example 1 of the present invention. Figure 8 The composition of crystal phases in different preparation stages and components was revealed in detail. After washing away sodium chloride, perovskite peaks appeared. LaCoO3 was successfully synthesized and has good crystallinity. A composite structure composed of LaCoO3 and SiO2 was successfully constructed.

[0083] Figure 9 The XRD pattern of the synthesis process of LaCoO3 in Example 1 of this invention is shown below. Figure 9 The composition of crystal phases in different preparation stages and components was revealed in detail. Perovskite peaks appeared after washing away sodium chloride. LaCoO3 was successfully synthesized and exhibits good crystallinity. Figure 9 It can be concluded that LaCoO3 was successfully synthesized.

[0084] Figure 10 This is the XRD pattern of the synthesis process of LaCoO3-CeO2 obtained without a NaCl template as described in Comparative Example 3 of the present invention. Figure 10 It can be seen that LaCoO3 has been successfully synthesized with good crystallinity, and a composite crystal phase of LaCoO3 and CeO2 has been synthesized. However, the diffraction peaks of LaCoO3 are more obvious, indicating that LaCoO3 may exist in a relatively independent or large-grained form, suggesting that the dispersion of LaCoO3 on the CeO2 support is limited without the addition of a NaCl template. In contrast, Figure 6 After adding a NaCl template and loading CeO2, the XRD pattern of the LaCoO3-CeO2-SLS sample mainly showed characteristic diffraction peaks of CeO2. This is because the small grain size of LaCoO3 and its good dispersion on the CeO2 support surface weaken its diffraction signal. This result indicates that the introduction of the NaCl template is beneficial to improving the dispersion state of the LaCoO3 active component on the CeO2 support surface, reducing obvious LaCoO3 crystal phase aggregation, and thus promoting a more sufficient interfacial contact between LaCoO3 and CeO2.

[0085] Figure 11 This is a comparison chart of the activity of 5%-LaCoO3-CeO2 prepared without a NaCl template in Comparative Example 3 and 5%-LaCoO3 / CeO2 prepared in Example 1, as shown in the figure. Figure 11 It can be seen that the T of the 5%-LaCoO3-CeO2-SLS catalyst prepared by the SLS method is... 90 The temperature is approximately 210℃. In comparison, the Tc of the LaCoO3 (NaCl-free)-CeO2 catalyst prepared without NaCl is... 90The temperature was significantly higher, approximately 280℃. This result clearly demonstrates that the 5%-LaCoO3-CeO2-SLS catalyst prepared with NaCl exhibits superior low-temperature CO oxidation activity, far exceeding that of the control sample prepared without NaCl.

[0086] Figure 12 This is the XRD pattern of the synthesis process of LaCoO3 obtained by impregnation method in Comparative Example 4 of the present invention. Figure 12 It is known that the impregnation method at low temperature calcination is unlikely to form the LaCoO3 phase, while it will form the Co3O4 phase. Theoretically, the impregnation method can adsorb LaCoO3 onto the CeO2 surface, but under low temperature conditions, it is difficult to form a crystallized perovskite phase, resulting in low particle dispersion and poor interfacial stability. This is consistent with the present invention. Figure 6 In comparison, the present invention is able to form the LaCoO3 crystalline phase.

[0087] Figure 13 The XRD pattern of the synthesis process of LaCoO3 obtained by precipitation method in Comparative Example 5 of the present invention is shown. Figure 13 It is known that precipitation methods are difficult to form the LaCoO3 phase, which is consistent with the present invention. Figure 6 In comparison, the present invention is able to form the LaCoO3 crystalline phase.

[0088] Figure 14 The results of synchrotron X-ray absorption spectroscopy analysis of the 5% LaCoO3 / CeO2 catalyst prepared in Example 1 of this invention are shown. Figure 14 (a) in the image is the La K-side Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum; Figure 14 (b) in the image is the X-ray absorption near-edge structure (XANES) spectrum of the Co K-edge; Figure 14 (c) in the image is the Co K-side Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum, obtained through... Figure 14 As shown in (a) the Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum (La K-edge), in the LaCoO3 / CeO2 composite material, the La atoms maintain their coordination environment within the perovskite structure; through Figure 14 As shown in (b) the X-ray absorption near-edge structure (XANES) spectrum (Co K-edge), the Co K-edge absorption edge in the LaCoO3 / CeO2 composite material shifts towards higher energies compared to pure LaCoO3, indicating an increase in the average valence state of Co. Figure 14As shown in (c) Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum (Co K-edge), the local coordination structure around the Co atom has changed to a certain extent, indicating that there is an interfacial interaction between LaCoO3 and CeO2. This interaction can regulate the electronic structure and local coordination environment of the Co site.

[0089] Figure 15 The results of aberration-corrected scanning transmission electron microscopy and electron energy loss spectroscopy measurements of the 5% LaCoO3 / CeO2 catalyst prepared in Example 1 of this invention are shown. Figure 15 As can be seen in (a) of the sample, there are clear nanostructure regions, indicating that LaCoO3 and CeO2 can form effective contact. Figure 15 (b) shows the distribution of the EELSM5 / M4 ratio in the corresponding region, where regions with higher M5 / M4 ratios correspond to higher proportions of Ce. 3+ Related species. (By) Figure 15 As can be seen in (b), a high M5 / M4 ratio is present at the interface or in local regions, indicating that after LaCoO3 and CeO2 recombine, the Ce valence state in the local CeO2 region changes, and more Ce is generated. 3+ Related species. Due to Ce 3+ The formation of oxygen vacancies is usually associated with oxygen vacancies, so this result suggests that more oxygen vacancies or local reduction sites may be formed at the LaCoO3-CeO2 interface.

[0090] Figure 16 This is a comparison of Ce 3d XPS spectra of the 5% LaCoO3- / CeO2 catalyst prepared in Example 1 of this invention and pure CeO2. Figure 16 It can be seen that CeO2 contains Ce 3+ The content was 17.21%, while the Ce content in the 5% LaCoO3-CeO2 sample was... 3+ The content increased to 22.39%. This result indicates that after LaCoO3 is combined with CeO2, the Ce content on the CeO2 surface increases. 3+ The increased proportion of related species indicates the formation of more oxygen vacancies or defect sites in the composite catalyst. Figure 14 and Figure 15 The results show that the LaCoO3 and CeO2 are not simply physically mixed, but form a heterogeneous interface with electronic structure interactions. This interface can regulate the electronic structure of Co and promote the formation of oxygen vacancies, which is beneficial to improving the ability of reactive oxygen species to migrate and the performance of CO oxidation at low temperatures.

[0091] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A method for preparing a CeO2-supported LaCoO3 metal oxide catalyst, characterized in that, Includes the following steps: Lanthanum and cobalt salts were ball-milled to obtain a metal salt mixture; then a template agent and an alkaline precipitant were added sequentially, and ball milling continued. The resulting ball-milled powder was calcined at 500℃~700℃ under normal pressure for 1h~3h to obtain LaCoO3 perovskite. The alkaline precipitant provides OH-... - The molar ratio of La to Co is 4.4~5.6:0.8~1.2:1.0; LaCoO3 perovskite and CeO2 nanoparticles were mixed and then added to deionized water for ultrasonic dispersion. The ultrasonic dispersion was centrifuged, washed and dried to obtain a CeO2-supported LaCoO3 metal oxide catalyst, wherein the mass ratio of LaCoO3 perovskite to CeO2 nanoparticles was 0.01~0.1:

1.

2. The method for preparing the CeO2-supported LaCoO3 metal oxide catalyst according to claim 1, characterized in that, Lanthanum salts and cobalt salts are both nitrates, chlorides, or acetates.

3. The method for preparing the CeO2-supported LaCoO3 metal oxide catalyst according to claim 2, characterized in that, The lanthanum salt and cobalt salt are chloride salts.

4. The method for preparing the CeO2-supported LaCoO3 metal oxide catalyst according to claim 1, characterized in that, The preferred molar ratio of lanthanum salt to cobalt salt is 1:

1.

5. The method for preparing the CeO2-supported LaCoO3 metal oxide catalyst according to claim 1, characterized in that, The template agent is one of potassium chloride, sodium bromide, or sodium chloride.

6. The method for preparing the CeO2-supported LaCoO3 metal oxide catalyst according to claim 1, characterized in that, The alkaline precipitant is sodium hydroxide or potassium hydroxide.

7. The method for preparing the CeO2-supported LaCoO3 metal oxide catalyst according to claim 1, characterized in that, The preferred mass ratio of LaCoO3 perovskite to CeO2 nanoparticles is 0.05:

1.

8. The method for preparing the CeO2-supported LaCoO3 metal oxide catalyst according to claim 1, characterized in that, OH provided by alkaline precipitant - The preferred molar ratio of La and Co is 5:1:

1.

9. The method for preparing the CeO2-supported LaCoO3 metal oxide catalyst according to any one of claims 1 to 8 yields the CeO2-supported LaCoO3 metal oxide catalyst.

10. The application of the CeO2-supported LaCoO3 metal oxide catalyst according to claim 9 in the CO oxidation reaction.